THEORETICAL JUSTIFICATION OF THE PARAMETERS OF THE ROLLER OF THE COMBINED UNIT - Mamatov, Farmon; Chuyanov, Dustmurod; Buriyev, Muhriddin; Ravshanova, Nargiza; Gulomov, Laziz (Innovatsion texnologiyalar, 2024)
In order to implement the proposed technology based on the analysis of the Patent and research work, it was found that in a combined aggregate it is necessary to apply a roller with a balloon attached to the frame.. Application of the spool the planting God flattens the surface of the field, grinding the incisions on the surface and compacting the soil. The article is theoretically based on the parameters of the combined aggregate reel, which prepares the soil for planting melon crops.